Evaluación de la fertilización nitrogenada y su efecto en el crecimiento y rendimiento en el cultivo de quinua (Chenopodium quinoa Willd.) en el Sector la Argelia, Cantón Loja - Sigcho González, Stefany Natali (2024)
Quinoa (Chenopodium quinoa), has been one of the most important grains for the Andean peoples, due to its high nutritional value as it has all the essential amino acids, on the other hand, this crop has been recognized for its great adaptability to different agro ecosystems. In spite of the fact that our country has all the favorable conditions for its cultivation, the yields achieved are low with a national average of 1 t ha-1. The factors that condition the increase in crop yield are not only climatic factors, but also those related to agronomic management, mainly nitrogen fertilization, since nitrogen is the main constituent of amino acids and chlorophyll, a pigment that allows plants to absorb light and convert it into energy needed for photosynthetic processes. Knowing the effect of nitrogen fertilization is necessary to maximize grain yield and improve fertilizer efficiency. In the present study, the effect of nitrogen on chlorophyll content, growth and yield was investigated. Five levels of nitrogen fertilization were used, from 0, 50, 100, 200 and 300 kg ha-1. Nitrogen and leaf chlorophyll content increased with doses of 200 and 300 kg N ha-1, exhibiting a positive relationship between these two variables, suggesting that chlorophyll content could be an important variable for predicting the nutritional status of N in the quinoa crop. The highest yield, number of grains per plant, number of grains m-2 and harvest index obtained were: 4.08 t ha-1, 22 629.79 grains per plant, 150 865.29 grains m-2 and 0.5 with 100 kg N ha-1. The agronomic efficiency of nitrogen was obtained with a dose of 100 kg N ha-1 to obtain 22.22 kg of grain for each kg of nitrogen applied.